2011
DOI: 10.3201/eid1710.110546
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculosis, People’s Republic of China, 2007–2009

Abstract: Early detection, effective treatment, and infection control measures are needed to reduce transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…Therefore, it can be expected that the 15-loci MIRU-VNTR technique may be a highly discriminatory tool for differentiating between clinical strains isolated from the region. However, the ETR-C locus showed very low diversity ( h  = 0.02) in this study, which is in agreement with several studies from other areas of China [4,7,38,39]. In contrast, ETR-C showed high discriminatory power in a study from Spain ( h  = 0.63) [5] and in another study from France ( h  = 0.71) [6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it can be expected that the 15-loci MIRU-VNTR technique may be a highly discriminatory tool for differentiating between clinical strains isolated from the region. However, the ETR-C locus showed very low diversity ( h  = 0.02) in this study, which is in agreement with several studies from other areas of China [4,7,38,39]. In contrast, ETR-C showed high discriminatory power in a study from Spain ( h  = 0.63) [5] and in another study from France ( h  = 0.71) [6].…”
Section: Discussionsupporting
confidence: 90%
“…First, our results likely overestimated the percentage of drug resistance compared with population-based studies because a greater proportion of seriously ill TB cases may be included in a hospital-based study. In contrast, the clustering rate of drug-resistant TB was likely underestimated in our one-year molecular epidemiologic survey because the clustering proportion depends on the completeness of sampling, where increasing sampling fractions will identify more clustering [39,41]. Second, twelve non-Beijing family isolates were categorised as “unknown” in the present study using a similarity search on the MIRU-VNTR plus website.…”
Section: Discussionmentioning
confidence: 99%
“…The MDR/RR-TB notification rate of farmers was higher than the rate of all other occupations and increased to 4.11 cases per 100,000 population in 2017. Our study showed that the occupation of farmer was associated with MDR/RR-TB, and some studies in other regions of China also showed that farmer was a risk factor [21]. In Chongqing, farmer was a poor occupation.…”
Section: Discussionsupporting
confidence: 58%
“…Although historically MDR-TB was thought to be predominantly created through treatment mismanagement, primary transmission has been identified as a large problem both in China and elsewhere (12)(13)(14). As person-to-person spread of drug resistance increases, identifying the efficacy of diagnostic tools in both new and previously treated cases may become more important.…”
Section: T Uberculosis (Tb) Is An Infectious Disease Caused By the Bamentioning
confidence: 99%